Over‐the‐counter hearing aids: What will it mean for older Americans?. Issue 7 (9th April 2022) - Blustein, Jan; Weinstein, Barbara E.; Chodosh, Joshua
Abstract: In October 2021 the Food and Drug Administration released draft rules creating a new class of hearing aids to be sold over the counter. Since Medicare does not cover hearing aids, the ready availability of low‐cost aids is potentially good news for the millions of older Americans with hearing loss, a disorder that is associated with isolation, depression and poor health. However, better financial access to hearing aids will not necessarily translate into better hearing: many older people will need assistance in fitting, using and maintaining their aids. Policymakers, managers, and clinicians need to consider how to structure, fund and deliver these vital adjunctive services. Abstract : See related editorial by Lin et al . in this issue.